Pembuatan Pupuk Kompos Kotoran Sapi Pada Petani Di Desa Pal IX, Kabupaten Kubu Raya - Leony Agustine; Urai Suci Y.V. Indrawati; Rini Hazriani; Rinto Manurung (Cv. Utility Project Solution, 2023)
Compost is organic material (organic waste) that has undergone a weathering process due to interactions between microorganisms (decomposing bacteria) working in it. Processing of livestock manure can be done by using livestock manure as manure. Pal IX Village, Sei Kakap District, Kubu Raya Regency, most of the people in this village live as rice and fruit vegetable farmers and there are some residents who raise cattle. The soil in this area is dominated by alluvial (tidal) soil which has chemical properties that are unfavorable for plant cultivation. This PKM aims to transfer the technology for making compost based on cow manure in Pal IX Village, Sei Kakap District, Kubu Raya Regency and to increase the ability of farmers to make compost and provide composting training. The implementation method is carried out by counseling presentations and direct manufacture of compost fertilizer. farmers are very enthusiastic and participate from the beginning of the activity to completion of this PKM activity.